1983
DOI: 10.1037/0096-3445.112.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of contingency between two dichotomous variables.

Abstract: Psychologists interested in such diverse areas as scientific reasoning, attribution theory, depression, and judgment have central tp their theories the ability of people to judge the degree of covariation between two variables. We performed seven experiments to help determine what heuristics people use in estimating the contingency between two dichotomous variables. Assume that the two variables are Factor 1 and Factor 2, each of which may be present or absent. In Experiment 1 we hypothesized that people assess Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
0
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 31 publications
11
153
0
4
Order By: Relevance
“…He found the best predictor of participants' judgment of covariation to be the present-present cell (both predictor and criterion present). Ward and Jenkins (1965), Shaklee and Tucker (1980), Shaklee and Mims (1982), and Arkes and Harkness (1983), using different methodologies, replicated the finding that the majority of participants' judgments are based on the present-present cell.…”
Section: Literature Review 23supporting
confidence: 71%
See 1 more Smart Citation
“…He found the best predictor of participants' judgment of covariation to be the present-present cell (both predictor and criterion present). Ward and Jenkins (1965), Shaklee and Tucker (1980), Shaklee and Mims (1982), and Arkes and Harkness (1983), using different methodologies, replicated the finding that the majority of participants' judgments are based on the present-present cell.…”
Section: Literature Review 23supporting
confidence: 71%
“…Third, the majority of the covariation research finding that participants used the either only the present-present cell Shaklee & Tucker, 1980;Shaklee & Mims, 1982;Arkes & Harkness, 1983) or both predictor present cells (Shaklee & Goldston, 1989;Shaklee & Hall, 1983) in making their covariation judgments.…”
Section: Hypothesis-focus Integration Bias Research Across Paradigmsmentioning
confidence: 99%
“…In particular, observation of the joint presence of the variables (Cell A) has the largest impact on judgments, and observation of the joint absence of the variables (Cell D) has the smallest impact. This has been shown by regressing strength judgments onto cell frequencies (Mandel & Lehman, 1998;Schustack & Sternberg, 1981) by asking participants directly which cells are most important (Crocker, 1982;Wasserman et al, 1990), by inferring cell importance and/or which rule participants use on the basis of patterns of responses (Arkes & Harkness, 1983;Levin, Wasserman, & Kao, 1993;Shaklee & Tucker, 1980;Wasserman et al, 1990), and by a meta-analysis of covariation research (Lipe, 1990). The impact of Cells B and C falls between that of Cells A and D (Crocker, 1982;Levin et al, 1993;Lipe, 1990;Wasserman et al, 1990).…”
Section: Covariation Assessmentmentioning
confidence: 99%
“…Arkes and Harkness (1983) reported that their subjects used a variety of heuristics depending on task characteristics. They concluded that "a search for the heuristic that people use will be a futile search" (p. 132).…”
Section: Linear-combination Heuristicsmentioning
confidence: 99%